Spiritual Warfare in Circulation - Marshall, Kimberly (Religions, 2020)
Without a doubt, an overenthusiastic focus on rupture, as a way of coping with neoliberal trauma, has shaped the conversation about recent religious change in Africa. Yet, rupture remains at the heart of what African charismatics understand themselves to be doing. In this paper, we attempt to nuance this conversation about rupture in religious change in Africa by discussing that various ontologies of spiritual warfare are encountered, made legible, reframed, and redeployed, through direct interactions between Africans and Americans in the context of missionization. We illustrate the patterns of these reciprocal flows through two case studies drawn from our larger research projects. One study illustrates the case of Matthew Durham, a young American missionary who, when accused of sexually assaulting children at an orphanage in Kenya, adopted the spiritual counsel of a Kenyan missionary that the reason he had no memory of the attacks was because of his possession by a demon. Another study discusses the example of a Navajo pastor who applied charismatic techniques of spiritual warfare when under metaphysical threat during a mission trip to Benin, but simultaneously focused on building ontologically protective social networks with Africans. Americans and Africans involved in the flows of global Pentecostalism are equally sympathetic to charismatic renewal. However, the reality of threats presented by malicious spiritual forces are echoed and amplified through concrete missionary networks that belie traditional North-South flows.